2015
DOI: 10.2298/tsci120328111c
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in square enclosures differentially heated at sides using alumina-water nanofluids with temperature-dependent physical properties

Abstract: Laminar natural convection of Al 2 O 3 + H 2 O nanofluids inside square cavities differentially heated at sides is studied numerically. A computational code based on the SIMPLE-C algorithm is used for the solution of the system of the mass, momentum, and energy transfer governing equations. Assuming that the nanofluid behaves like a single-phase fluid, these equations are the same as those valid for a pure fluid, provided that the thermophysical properties appearing in them are the nanofluid effective properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The results show that for increasing volume fractions there is certain rate of increase in heat transfer rate. Marta Cianfrini et al [16] analyzed the effect of size of the nanoparticles on heat transfer inside an enclosure filled with Al2O3/water nanofluid and reported that higher the size of the nanoparticles better is the heat transfer. Zoubair Boulahia et al [17] examined the combined effect of copperwater nanofluid and a cold obstacle on heat transfer performance of a square enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that for increasing volume fractions there is certain rate of increase in heat transfer rate. Marta Cianfrini et al [16] analyzed the effect of size of the nanoparticles on heat transfer inside an enclosure filled with Al2O3/water nanofluid and reported that higher the size of the nanoparticles better is the heat transfer. Zoubair Boulahia et al [17] examined the combined effect of copperwater nanofluid and a cold obstacle on heat transfer performance of a square enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide good understanding in circulation of cardiovascular system, design of solar collectors and geothermal systems. There are plenty of studies in enclosures with different geometries [1][2][3] under various conditions, like, radiation [4], external magnetic field [5], aspect ratio [6], variable fluid properties [7,8], and rotating rod [9]. Aich et al [1] examined natural convection in an isosceles prismatic enclosure and asymmetric flow structure is observed.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that nano uid type was a key factor in heat transfer enhancement, and CuO nanoparticles led to a better heat transfer rate than Al 2 O 3 nanoparticles did. Cianfrini et al [15] numerically studied the laminar natural convection of Al 2 O 3 -water nano uids inside square cavities. They found that when the nanoparticle volume fraction increased to an optimal particle loading, the amount of heat transfer of nano uids reached a peak across the enclosure.…”
Section: Introductionmentioning
confidence: 99%